Overcoming barriers to advanced biomolecular technologies that inform treatment of solid tumors: a roadmap to access - García-Foncillas, Jesús; Bayle, Arnaud; Arnold, Dirk; Avouac, Bernard; Awada, Ahmad; de la Cruz-Merino, Luis; Helland, Åslaug; Lassen, Ulrik; Laurent-Puig, Pierre; Normanno, Nicola; Rohrberg, Kristoffer; Taieb, Julien; et al. (Future oncology, 2025)
The advent of advanced biomolecular technologies for detecting molecular and genomic signatures of individual tumors has transformed oncology care, introducing proven methodologies that can inform treatment with matched targeted therapies and predict response at the individual patient level. However, access to these technologies has been hampered by multiple barriers, most notably price and obtainability. Other barriers include lack of knowledge of available technologies, concerns about value, and outdated infrastructures that impede critical operations within the clinic or laboratory. Accessibility barriers to advanced biomolecular testing are critically important to patient care, as new technological advances in molecular medicine continue to outpace the implementation of solutions. Given the proven evidence for improved patient outcomes with precision oncology medicines, it is imperative to understand the value afforded by these technologies. The purpose of this narrative review is to describe existing and emerging barriers to access and present a “roadmap to access” that will facilitate the urgently needed discussions to identify solutions for improving access. Implementation of these solutions will raise awareness of available technologies and treatments and their prognostic significance, improve evidence collection for demonstration of value, and fortify clinical and laboratory infrastructure and operations. New molecular technologies in medicine have made it possible to match oncology drugs to molecular markers found on individual tumors, such that patients can received more personalized treatments that specifically target their tumors. However, these technologies are often underused because of their high prices and challenges with obtaining them. Other concerns that have restricted their use include the lack of understanding about what they do or what benefits they offer, the logistics of introducing these technologies to clinics or labs, and questions about direct and indirect costs of their use versus potential cost-savings from selecting the best available treatment. Here we describe the current barriers that prevent patients and their healthcare providers from using these new technologies. We propose a “roadmap to access” to describe solutions which will enable access to these technologies. These solutions will benefit the healthcare community by improving the awareness of available technologies and understanding of how they improve health outcomes, demonstrate their value, and improve operations within clinics and laboratories.